‘Aaqilah in the Jurisprudence of the Four Schools of Thought (Ahl Al-Sunnah): A Comparative Jurisprudential Study - Hanif, Muhammad Wali (Journal of Humanities and Social Sciences Studies, 2023)
Among the punishments imposed by God Almighty for the felony of murder is the blood money, which is a financial penalty that the Lawgiver determined its amount, and it is large, so that the offender cannot bear it on his own, so the Lawgiver obligated the sane person to bear the blood money on behalf of the offender in the form of support and assistance. The clan initially bore the blood money, then Umar ibn al-Khattab, may God be pleased with him, transferred it to the people of the Diwan and the ministries. The tribes have disintegrated and families have separated, so the researcher sees the necessity of taking, according to Omar and the Hanafi school of thought, by charging the blood money to the people of the Diwan. He believes that some institutions can replace Diwan, such as ministries or the Social Security Authority, civil institutions such as trade unions and employees, or cooperative insurance companies. In studying this subject, I followed the descriptive, analytical and comparative approach, where I explained the concept of rationality, its reality, the sayings of the four schools of thought in each issue, and the statement of the most correct.